Shared Medical Appointments: Implementing Diabetes SMAs to Improve Care for High Risk Patients and Maximize Provider Expertise - Kirsh, Susan; Lawrence, Renée; Stevenson, Lauren; Watts, Sharon; Schaub, Kimberley; Aron, David; Pascuzzi, Kristina; Strauss, Gerald; O'Day, Mary Ellen (IntechOpen, 2012)
None